ANALISIS NILAI KEPADATAN LAPANGAN DENGAN SAND CONE TEST (STUDI KASUS: JALAN YOS SUDARSO KOTA PALANGKA RAYA) - Vingnesia Vingnesia; Fatma Sarie; Suradji Gandi (INFO-TEKNIK, 2021)
Soil compaction is required so that the embankment is strong and balanced with structural and non-structural loads. One of the efforts to handle soil with low bearing capacity is to change the subgrade using soil that is considered good. Therefore, an attempt was made to estimate the density of the soil in the field by conducting a sand cone test on the selected embankment material on the Yos Sudarso road work, Palangka Raya City. The sample used in this study came from Hampangen Village, Kasongan Baru Village, Katingan Hilir District, Katingan Regency, Central Kalimantan Province. The results of tests carried out on laboratory density testing and sand cone testing on Yos Sudarso Street, Palangka Raya City can be ascertained that the density obtained from dry soil density γdry = 1.29 g/cm3, maximum dry density γd lab = 1.35 g/cm3 γdr / γd lab x100 = Dr. So the approved density is Dr = 95.86%.